Marked as Homeless: Reconciling with Ambiguities about Housing Status in Death Records. (September 2022) - Greene, R. Neil
Research on the process of classification has long revealed biases and limitations embedded within social data. Expanding or contracting definitions of homelessness and the perception of housing status as relevant information play a large part in data and knowledge about homelessness. The author explores how homelessness is conceptualized and documented (or not documented) within death records through the use of qualitative interviews with field investigators ( n = 20) who attend and document circumstances related to suspicious deaths in New Mexico. The findings reveal uncertainty in marking a person as homeless that is newly described as labeling ambivalence, which can be resolved more systematically through a process of increasing social mattering in which the social determinants of health are accentuated as factors related to premature mortality. The findings suggest important considerations for more systematically describing housing status and other indicators of the social determinants of health within social records.